1985
DOI: 10.1136/bmj.290.6472.881
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical staining of breast carcinoma with the monoclonal antibody NCRC 11: a new prognostic indicator.

Abstract: The staining of breast cancer with a new monoclonal antibody, NCRC 11, was studied in a series of 126 women with primary breast carcinoma. Tumour samples embedded in paraffin were tested, and the minimum duration of follow up was five years or to death. Altogether 119 tumours stained positively. There was a strong relation between the intensity of staining, divided on a four point scale, and patient survival. Patients whose tumours exhibited intense staining had an improved survival compared with those with le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 9 publications
(4 reference statements)
2
34
1
Order By: Relevance
“…Although, increased expression of MUC1 in conventional carcinoma correlated with low-grade cytology and good prognosis, [22][23][24][25][26] aberrant expression such as intracytoplasmic localization was shown by multiple studies to be associated with poor outcome, independent of tumor differentiation. [26][27][28][29][30] Intercellular/circumferential labeling was associated with a high incidence of lymph node metastases as well.…”
Section: Muc1 In Invasive Micropapillary Carcinoma H Nassar Et Almentioning
confidence: 99%
“…Although, increased expression of MUC1 in conventional carcinoma correlated with low-grade cytology and good prognosis, [22][23][24][25][26] aberrant expression such as intracytoplasmic localization was shown by multiple studies to be associated with poor outcome, independent of tumor differentiation. [26][27][28][29][30] Intercellular/circumferential labeling was associated with a high incidence of lymph node metastases as well.…”
Section: Muc1 In Invasive Micropapillary Carcinoma H Nassar Et Almentioning
confidence: 99%
“…The synthesis of EMA by mammary acini and ducts is thought to be a specialised function and therefore tumours which contain EMA in abundance may be better differentiated and hence have a better prognosis than those in which it is less plentiful. In two studies using NCRC-1 and an immunoperoxidase method a relationship was demonstrated between well stained tumours and a favourable prognosis (Ellis et al, 1985. In a smaller study this relationship could not be confirmed (Angus et al, 1986) and no such study has been undertaken for 3E1.2.…”
mentioning
confidence: 99%
“…Immunoperoxidase staining patterns of primary breast tumours using monoclonal antibody have been shown to relate to overall survival (Ellis et al, 1985) but the results have not been reproducible in other centres. In this study paraffin sections of 483 primary breast cancers were stained with NCRC-11 and 3E1.2 using an immunoperoxidase system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This antibody reacts with a variety of normal and malignant tissues of epithelial origin and immunocytochemical studies have shown that in malignant tissue there exists a direct relationship between the intensity of staining and patient survival (Ellis et al, 1985). The antigen defined by NCRC-l bears multiple epitopes for several anti-mucin MAbs and also displays the same molecular weight, tissue distribution and genetic polymorphism as PEM.…”
mentioning
confidence: 99%